Kreativitas Guru dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 2 Merangin - Bulkoini, Bulkoini (Edification Journal : Pendidikan Agama Islam, 2022)
This research is motivated by the not yet optimal creativity of technicians in learning Islamic religious education at SMPN 2 Merangin. This study uses a qualitative approach that is descriptive analytical. Data was collected by using observation,interview and documentation techniques. The results showed that: 1) teachers were very creative in using varied learning methods in planning lesson plans so that students were more enthusiastic about learning and not easily bored, 2) the creativity of teachers in using varied learning resources. utilization of learning resources for the learning process, 3) the creativity of teachers in evaluating learning at SMPN 2 Merangin is by conducting tests on students. There are oral and written tests. 4) the creativity of teachers in the first, preparing mentally and physically to participate in the learning process, second, providing contextual student motivation according to the benefits and applications of teaching materials in everyday life.